2020
DOI: 10.1093/eurpub/ckaa193
|View full text |Cite
|
Sign up to set email alerts
|

Trends in adolescent drinking across 39 high-income countries: exploring the timing and magnitude of decline

Abstract: Background Evidence suggests adolescent alcohol consumption has declined since the turn of the millennium in almost all high-income countries. However, differences in the timing and magnitude of the decline have not been explored across countries. Methods We examined trends in adolescent past month or monthly alcohol consumption prevalence from cross-national or national survey reports for 39 countries and four US territories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 23 publications
6
58
0
1
Order By: Relevance
“…Since 2013, when the prevalence of drinking dropped to 47 per cent, drinking is no longer the majority behaviour among Swedish ninth graders. Similar trends have been observed in most western countries [19][20][21][22]. Against this background with trends of declining drinking and increase of non-drinkers that has been so marked that it has also led to a shift in the majority behaviour, there is a need to assess what the changing social status of drinking implies for our understanding of non-drinking in adolescence.…”
Section: Introductionsupporting
confidence: 53%
“…Since 2013, when the prevalence of drinking dropped to 47 per cent, drinking is no longer the majority behaviour among Swedish ninth graders. Similar trends have been observed in most western countries [19][20][21][22]. Against this background with trends of declining drinking and increase of non-drinkers that has been so marked that it has also led to a shift in the majority behaviour, there is a need to assess what the changing social status of drinking implies for our understanding of non-drinking in adolescence.…”
Section: Introductionsupporting
confidence: 53%
“…A list of key behaviours and outcomes was generated based on previous studies examining multiple adolescent behaviours and outcomes [11,20]. To identify the relevant data sources, a systematic search was conducted based on following criteria: (i) nationally representative Australian data or reliable administrative data focussed on adolescents (ranging from age 10–19 years); (ii) data available from the year 2000 onwards to focus on the time‐period during which the decline in drinking or decline in substance use or other risky behaviours have been reported in research studies from other countries [22]; and (iii) data sources containing at least two time points. In cases where multiple data sources for any adolescent behaviour or outcome were available, the source with longer time period data from 2000 to 2019 was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…Longitudinal studies have clearly demonstrated that foetal alcohol exposure was associated with alcohol problems in early adolescence (even after controlling for family history of alcoholism, prenatal nicotine exposure, parenting style, current parental drinking, household stress, and self-esteem) ( 45 ) and young adulthood ( 46 ). Thus, although there has been a demonstrable overall reduction in adolescent drinking worldwide ( 47 ), this does not hold true for the offspring of mothers who used alcohol during pregnancy.…”
Section: Metabolic Influences In the Perinatal Period And The Risk On The Offspringmentioning
confidence: 99%